1982
DOI: 10.1177/030098588201907s09
|View full text |Cite
|
Sign up to set email alerts
|

Acute Gastric Dilatation in Nonhuman Primates: Review and Case Studies

Abstract: Abstract. Acute gastric dilatation occurs sporadically in laboratory-housed nonhuman primates. Clinical histories often include chronic drug administration, food restriction, accidental overfeeding, and prior anesthesia. Monkeys may be found dead or may have clinical signs of colic, abdominal distention, and dyspnea. Death in untreated cases is due to impaired venous return and cardiopulmonary failure. Gastric distention with fermented gaseous ingesta and congestion of the abdominal viscera are the predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 7 publications
0
25
0
1
Order By: Relevance
“…Thus, there may be animal selection issues associated with experimentally manipulated changes in diet. Care must also be taken to prevent animals from overeating following a period of food restriction, as gastric dilation may result (Pond et al 1982). Finally, longterm controlled caloric restriction was shown to have beneficial effects on morbidity, insulin sensitivity, and mortality in rhesus monkeys (Bodkin et al 2003).…”
Section: Dietmentioning
confidence: 99%
“…Thus, there may be animal selection issues associated with experimentally manipulated changes in diet. Care must also be taken to prevent animals from overeating following a period of food restriction, as gastric dilation may result (Pond et al 1982). Finally, longterm controlled caloric restriction was shown to have beneficial effects on morbidity, insulin sensitivity, and mortality in rhesus monkeys (Bodkin et al 2003).…”
Section: Dietmentioning
confidence: 99%
“…However, we found an increase in the consumption time in the puzzle feeder condition that was probably due to the novelty of the puzzle feeder. It has previously been reported that some monkeys are in danger of serious problems, such as acute gastric dilatation (AGD), due to food restriction or accidental over feeding [12], as well as altered feeding schedules [3,10]. To the author's knowledge, many monkeys that are housed individually at laboratory facilities die because of AGD regardless of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In macaques, AGD was first reported in 1967 [11]. In his clinico-pathological studies of gastrointestinal diseases in macaques, conducted over a 2-yr period with 335 animals, Holmberg [1] reported that AGD represented 12% (7 of 57) of the deaths from enteric disease and 2% (7 of 335) of the total deaths evaluated.…”
Section: Agd In Non-human Primatesmentioning
confidence: 99%